Effect of nano-ZrC powders on microstructure and properties of 90W−7Ni−3Fe alloys - SU Xuwen; HE Zhi; YAN Shuxin; DONG Longlong; SUN Guodong (Fenmo yejin jishu)
To effectively inhibit the growth of tungsten grains during the liquid phase sintering, the ZrC dispersion-strengthened heavy tungsten alloys (WHAs) were prepared by liquid phase sintering at 1500 ℃. The effects of ZrC mass fraction (1% and 2%) on the microstructure and properties of WHAs were analyzed. The results show that, with the increase of ZrC mass fraction, the relative density and W−W contiguity of WHAs decrease, and the tungsten grains are refined to a certain extent. When the ZrC mass fraction is 1%, the strength-ductility matching effect of WHAs is the best, the relative density reaches 98.4%, the tungsten grain size is 22.17 μm, and the yield strength and compressive strength (40% deformation) reach 791 MPa and 2179 MPa, respectively, which are increased by 8.35% and 38.70%, compared with WHAs without ZrC (730 MPa and 1570 MPa).